Green jobs and the city: Towards a just transition in developing countries - Alexander Kleibrink; Anna Pegels; Michael Fink; Wolfgang Scholz (German Institute of Development and Sustainability (IDOS), 2023)
This policy brief examines actions for a just transition of local job markets in developing countries. We identify building blocks for shifting from carbon-intensive towards green jobs in this transition. Green jobs in cities are key to ensure a just transition of local employment markets, both formal and informal, and make cities function more sustainably. They are part of a wider inclusive green economy aiming at carbon-neutrality and resource efficiency with a focus on human well-being and social equity while paying special attention to local nature-based solutions. The transition will create winners and losers. Both need to be managed if the process and outcomes are to be just.
Keywords: 320; Green jobs; urbanisation; just transition; developing countries; climate change